The Influence Of Government Accounting Standards (Sap) Implementation, Good Governance, And The Use Of Information Technology On The Quality Of Financial Reports At Bpkpad Binjai City - Vildo Rizky Kurniadi; Vina Arnita; Hendra Saputra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to examine the extent to which the implementation of SAP (Government Accounting Standards), Good Governance, and the utilization of information technology affect the quality of financial reports at the BPKPAD of Binjai City. A descriptive quantitative approach was used in this research, with a sample of 80 respondents taken from 189 employees using purposive sampling techniques. Data collection instruments included observation, questionnaires, and literature study, which were then processed using multiple linear regression techniques. The results of the data analysis show a positive and significant influence from the implementation of SAP, Good Governance, and information technology on the quality of financial reports, both partially and simultaneously.